2021
DOI: 10.3390/ijms23010111
|View full text |Cite
|
Sign up to set email alerts
|

From Molecules to Behavior in Long-Term Inorganic Mercury Intoxication: Unraveling Proteomic Features in Cerebellar Neurodegeneration of Rats

Abstract: Mercury is a severe environmental pollutant with neurotoxic effects, especially when exposed for long periods. Although there are several evidences regarding mercury toxicity, little is known about inorganic mercury (IHg) species and cerebellum, one of the main targets of mercury associated with the neurological symptomatology of mercurial poisoning. Besides that, the global proteomic profile assessment is a valuable tool to screen possible biomarkers and elucidate molecular targets of mercury neurotoxicity; h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 71 publications
0
13
0
1
Order By: Relevance
“…The proteomic data analyses were only possible due to the comparability between the samples within the same group, and the use of Protein Lynx GlobalSERVER software, robust software for data analyses, was able to determine the p values, hence the quantitative proteomic analysis, considering p < 0.05 for downregulated proteins and 1 − p > 0.95 for upregulated proteins. Detailed methodology is available elsewhere [ 11 , 66 , 86 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteomic data analyses were only possible due to the comparability between the samples within the same group, and the use of Protein Lynx GlobalSERVER software, robust software for data analyses, was able to determine the p values, hence the quantitative proteomic analysis, considering p < 0.05 for downregulated proteins and 1 − p > 0.95 for upregulated proteins. Detailed methodology is available elsewhere [ 11 , 66 , 86 ].…”
Section: Methodsmentioning
confidence: 99%
“…Al has no biological function in humans; moreover, prolonged exposure to Al may be associated with hematopoietic, skeletal, respiratory, immunological, neurological, and functional adverse effects [ 8 ]. Since Al-induced toxic effects are evidenced in vitro [ 9 ], in humans [ 10 ], and animal studies [ 11 ], this element has received considerable attention mainly due to its neurotoxic abilities. These effects are prominent and have been associated with neurodegenerative diseases, especially Alzheimer’s disease (AD) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This profile guarantees the translational value of this work, standing out in the current literature as a more realistic approach when compared to other studies. For instance, cerebellar cortex is one of the most affected regions in humans chronically contaminated by Hg (Eto et al [103] ), a pattern also observed in rats submitted to a long-term intoxication (Bittencourt et al [104] ). Therefore, although it is important to bear in mind that the physiological particularities between humans and rats should be considered when evaluating the results of studies using animal models [105] , this study took advantage of the improvement recommendations that were previously suggested to have a significant and differentiated translational value within the current literature.…”
Section: Discussionmentioning
confidence: 99%
“…For evaluation of Purkinje cell density, the sections obtained by microtomy were stained by routine hematoxylin–eosin (HE) and then analyzed by light microscopy (Nikon Eclipse E200, Tokyo, Japan), using a grid corresponding to an area of 0.0625 mm 2 coupled to one of the eyepieces, using an objective lens with 40× magnification. At least three fields in the cerebellum per section and one section per animal of each group were analyzed to count the number of Purkinje neurons per field [ 49 ].…”
Section: Methodsmentioning
confidence: 99%